2010
DOI: 10.21273/hortsci.45.10.1522
|View full text |Cite
|
Sign up to set email alerts
|

Organic Soil Amendment and Tillage Affect Soil Quality and Plant Performance in Simulated Residential Landscapes

Abstract: The urban soil environment is usually not conducive to healthy root growth and function, leading to problems with plant establishment, growth, and aesthetic quality. The objective of this study was to determine if the addition of compost with or without the application of shallow tillage or aeration will improve soil physical and chemical properties and plant growth compared with an unamended control in simulated new residential landscapes. Twenty-four mixed landscape plots were established in a random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…The findings of this study agrees with those of Goyal et al [13] who reported an increase in the total soil nitrogen after application of both the organic and inorganic amendments in the cropping field. Both organic and inorganic amendments contributes to an increased supply of key mineral nutrients like nitrogen hence making them available in the soils as reported by Loper et al [14]. This study results also agree with findings of Wuest and Gollany (CM) treatment led to the highest increase of N (recording 0.40 %).…”
Section: Influence Of Organic and Inorganic Amendments On Soil Total supporting
confidence: 92%
“…The findings of this study agrees with those of Goyal et al [13] who reported an increase in the total soil nitrogen after application of both the organic and inorganic amendments in the cropping field. Both organic and inorganic amendments contributes to an increased supply of key mineral nutrients like nitrogen hence making them available in the soils as reported by Loper et al [14]. This study results also agree with findings of Wuest and Gollany (CM) treatment led to the highest increase of N (recording 0.40 %).…”
Section: Influence Of Organic and Inorganic Amendments On Soil Total supporting
confidence: 92%
“…Soil organic amendments are commonly recommended for improving highly disturbed urban 432 soils and are particularly recommended for reducing soil compaction (Cogger, 2005;Saebø and 433 Ferrini, 2006;Larney and Angers, 2012;Sloan et al, 2012). While organic soil amendments 434 immediately decrease ρ b through a bulk dilution of mineral soil with organic material (Bassuk and Rivenshield, 2007;Loper et al, 2010), the persistence of this effect has been questioned. In 436 the Arlington study, the small decreases in ρ b were likely due to this dilution effect, as aggregate formation usually takes longer than the 13 months between installation and sampling (Wick et al, 438 2009a).…”
Section: Discussionmentioning
confidence: 99%
“…This was due to the liming and buffering effect of CACO3 in cow manure [47,48]. Moreover, the nature of amendments affects the pH, thus if the applied amendment has a low pH, it will affect the pH of the soil and vice versa [49]. The high pH in the organic amended fields could have been due to any of the under mentioned mechanisms or combinations; proton consumption during the removal of carboxyl groups from the organic acids anions which occur during decomposition [50], proton consumption by functional groups associated with the organic materials [51] and the release of hydroxide ions from local anaerobic microsites during reduction reactions [52].…”
Section: The Variation Of Soil Ph and Electrical Conductivity Under Tmentioning
confidence: 99%